ℒ1 adaptive control of quadrotor UAVs in case of inversion of the torque direction - Souanef, Toufik; Whidborne, James F.; Boubakir, Ahsene (SCIE Publish, 2024)
This paper presents a method for fault tolerant control of quadrotor UAVs in case of inversion of the torque direction, a situation that might occur due to structural, hardware or software issues. The proposed design is based on multiple-model ℒ1 adaptive control. The controller is composed of a nominal reference model and a set of degraded reference models. The nominal model is that with desired dynamics that are optimal regarding some specific criteria. In a degraded model, the performance criteria are reduced. It is designed to ensure system robustness in the presence of critical failures. The controller is tested in simulations and it is shown that the multiple model ℒ1 adaptive controller stabilizes the system in case of inversion of the control input, while the ℒ1 adaptive controller with a single nominal model fails.
Keywords: ℒ1 adaptive control; Quadrotor control; Fault-tolerant control